Valve cover forge piece structure with high sealing performance - LIN WEIZHONG; CHEN WANZHU (2024)
The utility model relates to the technical field of valve decks, in particular to a high-sealing-performance valve deck forge piece structure which comprises a valve deck and a first flange, the outer wall of the top of the valve deck is fixedly connected with the first flange, the outer wall of the bottom of the valve deck is fixedly connected with a second flange, and the bottom of the valve deck is fixedly connected with a sealing ring. The bottom of the sealing ring is attached to the valve body, a connecting groove is machined in the bottom of the sealing ring, and a sealing structure is arranged on the top of the sealing ring. The limiting block is pushed to move downwards through the elastic force of the spring, the limiting block drives the sliding block to move downwards, the sliding block drives the rubber pad to move downwards along the sliding groove of the sealing ring, and the gap between the circular ring and the rubber pad is compensated, so that the sealing performance between the valve cover